A lesson from the introduction of a problem-based, graduate entry course: the effects of different views of self-direction. - Miflin BM; Campbell CB; Price DA (Medical Education, 1999)
OBJECTIVES: Difficulties in the early years of a new curriculum are to be expected as staff and students come to terms with new structures, and with different approaches to teaching and learning. During the first year of implementation of the Graduate Medical Course at the Graduate School of Medicine, The University of Queensland, we experienced our share of 'teething troubles'. One source of difficulty was different interpretations of the concept of 'self-directed learning' as it was to be applied in the new course. This paper presents an analysis of the effects of these differences on the development of the curriculum. DESIGN: An orientation programme was designed to introduce students to staff, facilities and the PBL process. SETTING: The University of Queensland. SUBJECTS: Problem-based learning (PBL) tutors, medical students. RESULTS: The overall effect was to place in jeopardy the achievement of student self-direction and commitment to lifelong learning as a goal of the course. To counter the undesirable effects of different interpretations, we have developed a conceptual framework to promote an agreed understanding of the meaning of self-direction, and to guide review and further development of the curriculum. A further paper describes the framework. CONCLUSIONS: Consistency in interpretation of key concepts is an important factor in the success of problem-based curricula.